Plasma Polymerization of Acrylic Acid for the Tunable Synthesis of Glassy and Carboxylated Nanoparticles - Pleskunov, Pavel; Nikitin, Daniil; Tafiichuk, Renata; Shelemin, Artem; Hanuš, Jan; Kousal, Jaroslav; Krtouš, Zdeněk; Khalakhan, Ivan; Kúš, Peter; Nasu, Tatsuro; Nagahama, Tomoki; Funaki, Chihiro; et al. (The journal of physical chemistry. B, 2020)
Polymer nanoparticles (NPs) can be highly attractive in numerous applications, including biomedicine, where the use of inorganic matter may be detrimental for living tissues. In conventional wet chemistry, polymerization and functionalization of NPs with specific chemical groups involves complex and often numerous reactions. Here, we report on a solvent-free, single-step, low-temperature plasma-based synthesis of carboxylated NPs produced by the polymerization of acrylic acid under the conditions of a glow discharge. In a monomer-deficient regime, the strong fragmentation of monomer molecules by electron impact results in the formation of 15 nm-sized NPs with <1% retention of the carboxyl groups. In an energy-deficient regime, larger 90 nm-sized NPs are formed with better retention of carboxyl groups that reaches 16%. All types of NPs exhibit a glass transition above room temperature, which makes them highly stable in an aqueous environment with no dissolution or swelling. The NPs are also found to degrade thermally when heated above 150 °C, with a decrease in the mean NP size but with retention of the chemical composition. Thus, plasma polymerization proves to be a versatile approach for the production of polymer NPs with a tunable size distribution, chemical composition, and physical properties.
Keywords: velikost částic; akrylové pryskyřice; plazmové plyny; nanočástice; Particle Size; Nanoparticles; polymerizace; akryláty; Acrylates; Acrylic Resins; Plasma Gases; Polymerization